Trial conducted in short order (Journal of actual problems of jurisprudence, 2018)
The paper considers the role of the judicial proceedings conducted in short order. Expeditednotcontraryocnovnymprinciplesof criminal procedure, and the reduction ofthe accelerationof the proceedingsinthemainstage ofthe proceedings,namely thereduction ofthe judicial investigation,absolutelynot be tolerated.The rapidityof the proceedingscan not andshould notprotivopos-nent of comprehensiveness, completeness,objectivity, examining allrelevant to thecircumstances ofthe case.Keywords: trial, reduced order.